Zwitterionic composite hydrogel adhesive and preparation method thereof
By combining materials such as AMPS, SBMA and PVA and performing radical polymerization, zwitterionic composite hydrogel adhesive was prepared, which solved the problem of insufficient mechanical properties and adhesion of existing hydrogels, achieved higher tensile strength and adhesion, and broadened its application potential in the medical field.
Patent Information
- Application Number
- CN202411843813.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-14
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-14
AI Technical Summary
The existing zwitterionic hydrogels have poor mechanical properties and adhesion, making it difficult to meet complex and changeable medical needs.
Zwitterionic composite hydrogel adhesive was prepared by combining anionic monomer AMPS with a bilayer network of zwitterionic SBMA and polyvinyl alcohol (PVA).
It improves the tensile strength and adhesion of the hydrogel, enhances its mechanical properties and biological activity, and gives it a wider application potential in the medical field.
Smart Images

Figure CN119661783A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of bioadhesive development and relates to a zwitterionic composite hydrogel adhesive and a preparation method thereof. Background Art
[0002] The research field of medical adhesives is broad and in-depth, aiming to continuously overcome the limitations of traditional adhesives. For example, the cyanoacrylate-based adhesive disclosed in Patent No. CN202211429820.3, although excellent in some aspects, faces problems such as insufficient elasticity of the bonding site, short storage life, and easy solidification, which greatly limits its scope and effect in practical applications. Similarly, the fibrin adhesive described in Patent No. CN202310060671.6, although it has advantages such as biocompatibility, also has defects such as low bonding strength and low hardness, which makes it difficult to meet complex and changing medical needs.
[0003] In this context, hydrogel, as a unique semi-solid substance, is regarded as a polymer material that is highly similar to human soft tissue because of its three-dimensional network structure and rich hydrophilic groups. Among them, zwitterionic hydrogels have shown broad application prospects in many fields such as flexible sensing, biomaterials, and medical engineering due to their unique properties such as high ion density and ion sensitivity. However, despite the many advantages of zwitterionic hydrogels, their mechanical properties are relatively weak, their adhesion level needs to be improved, and their comprehensive performance cannot fully meet the needs of practical applications. In addition, due to these limitations, the application scenarios of zwitterionic hydrogels are relatively single, and it is difficult to realize their potential in a wider range of medical fields. Therefore, how to further improve the mechanical properties and adhesion ability of zwitterionic hydrogels and broaden their application scenarios is an important issue that needs to be urgently solved in the current research field of medical adhesives. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a zwitterionic composite hydrogel adhesive and a preparation method thereof, thereby solving the technical problems of poor mechanical properties and adhesion of zwitterionic hydrogels in the prior art.
[0005] The present invention is achieved through the following technical solutions: A method for preparing a zwitterionic composite hydrogel adhesive comprises the following steps: S1: Dissolve the reaction monomers SBMA and AMPS in water, and ultrasonically oscillate them at room temperature to fully dissolve them. Then add THMA, stir until the mixture is evenly mixed, then add the initiator and cross-linking agent, and ultrasonically dissolve them to obtain a precursor solution. S2: adding the PVA aqueous solution to the precursor solution to carry out a free radical polymerization reaction to obtain the zwitterionic composite hydrogel adhesive.
[0006] Preferably, the ratio of the reaction monomers SBMA and AMPS is (9-5):(1-5) in terms of mass fractions.
[0007] Preferably, the ratio of THMA to SBMA and AMPS is 1:(9-5):(1-5) by weight.
[0008] Preferably, the ratio of PVA to SBMA and AMPS is 20:(9-5):(1-5) by weight.
[0009] Preferably, the ratio of SBMA to AMPS and initiator is (25-13):(2-13):1 in terms of mass fractions.
[0010] Preferably, the ratio of SBMA to AMPS and the cross-linking agent is (300-160):(30-160):1 in terms of mass fractions.
[0011] Preferably, the cross-linking agent is N,N'-methylenebisacrylamide and borax; in terms of mass fractions, the ratio of N,N'-methylenebisacrylamide to borax is (1-5):(1-10).
[0012] Preferably, the preparation process of the PVA aqueous solution is: dissolving PVA in water, heating and stirring at 90-100° C. for 5-8 hours to obtain the PVA aqueous solution. Preferably, the reaction temperature of the free radical polymerization reaction is 35-45° C., and the reaction time is 10-15 h.
[0013] A zwitterionic composite hydrogel adhesive is prepared by the above method; the zwitterionic composite hydrogel adhesive has a tensile strength of 0.07-0.14 MPa and an adhesion force of 20-33 Kpa.
[0014] Compared with the prior art, the present invention has the following beneficial technical effects: The invention discloses a method for preparing a zwitterionic composite hydrogel adhesive. The method comprises combining anionic monomer 2-acrylamide-2-methylpropane sulfonate (AMPS) into a double-layer network of zwitterionic ([2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl) ammonium hydroxide, SBMA) and polyvinyl alcohol (PVA), adding N-[tris(hydroxymethyl)methyl]acrylamide (THMA) reactive monomer during the reaction to provide hydrogen bonding for the polymer, thereby further promoting adhesion, and preparing the zwitterionic composite hydrogel adhesive through a one-pot method. Polyvinyl alcohol (PVA) has abundant cross-linking sites and multiple hydrogen bonds. Zwitterionic SBMA has cationic and anionic groups and has a high dipole moment. This strong dipole moment forms adhesion with many surfaces through ion-dipole or dipole-dipole interactions, and the chain-chain association between the polymers can provide physical cross-linking to enhance the mechanical properties of the water adhesive. The reactive monomer N-[tris(hydroxymethyl)methyl]acrylamide (THMA) can provide hydrogen bonding for the polymer, thereby further promoting adhesion. The zwitterionic composite hydrogel adhesive of the present invention is safe, simple, easy to operate and low in cost. The adhesive has a fast gelling speed, is easy to operate, can achieve rapid adhesion, and has high adhesion strength on the epidermis, and is suitable for applications such as bonding of sensing materials and wound hemostasis and adhesion. The PVA used in the present invention has abundant cross-linking sites and multiple hydrogen bonds, which helps to enhance the performance of the hydrogel. The reactive monomer SBMA has cationic and anionic groups, and the overall electrical neutrality is maintained. This strong dipole property forms adhesion with a variety of surfaces through ion-dipole or dipole-dipole interactions, and the association between its polymer chains can provide physical cross-linking, thereby enhancing the mechanical properties of the water adhesive. AMPS, as an anionic monomer, can improve the electrical conductivity of the system. The zwitterionic composite hydrogel prepared by the present invention is not easy to affect bioactive substances, so it shows good biological activity in tissue engineering, so that it has a wide range of application potential in the field of biomedicine.
[0015] Furthermore, in terms of mass fractions, the ratio of the reaction monomers SBMA and AMPS is (9-5):(1-5), which effectively ensures the adhesion performance of the hydrogel and improves the mechanical properties.
[0016] Furthermore, the ratio of THMA to SBMA and AMPS is 1:(9-5):(1-5) by weight, which can improve the adhesion of the hydrogel.
[0017] Furthermore, the ratio of PVA to SBMA and AMPS is 20:(9-5):(1-5) by weight, which can improve the degree of network cross-linking.
[0018] Furthermore, in terms of mass fractions, the ratio of SBMA to AMPS and initiator is (25-13):(2-13):1, which effectively ensures that the cross-linking reaction is fully carried out.
[0019] Furthermore, in terms of weight fractions, the ratio of SBMA to AMPS and the cross-linking agent is (300-160):(30-160):1, which allows the monomers to undergo sufficient cross-linking reaction.
[0020] Furthermore, the crosslinking agent is N,N'-methylenebisacrylamide and borax; in terms of mass fraction, the ratio of N,N'-methylenebisacrylamide to borax is (1-5):(1-10), N,N'-methylenebisacrylamide can form covalent bonds with monomer molecules during polymerization, thereby constructing a tight chemical crosslinking network, and borax can release borate ions in aqueous solution, which can form ionic crosslinks with functional groups (such as hydroxyl, carboxyl, etc.) on the polymer chain to construct an ionic crosslinking network. The two crosslinking agents work together to form a double crosslinking network structure, so that the hydrogel has higher strength and stability; by adjusting the ratio of N,N'-methylenebisacrylamide to borax, the crosslinking density of the hydrogel can be regulated, a higher crosslinking density can improve the mechanical strength and wear resistance of the hydrogel, while a lower crosslinking density may give the hydrogel better flexibility and elasticity, and this regulation ability enables the hydrogel to meet the needs of different application scenarios.
[0021] Furthermore, the preparation process of the PVA aqueous solution is: dissolving PVA in water, heating and stirring at 90-100° C. for 5-8 hours to obtain the PVA aqueous solution, which can improve the degree of cross-linking of the system. Furthermore, the reaction temperature of the free radical polymerization reaction is 35-45°C, and the reaction time is 10-15h. Setting the reaction temperature within the range of 35-45°C not only ensures the reaction rate, but also avoids the side reactions and product degradation that may be caused by excessively high temperatures. This temperature range helps the monomer molecules to fully dissolve and diffuse, promotes the chain growth reaction, and thus improves the efficiency of the polymerization reaction and the molecular weight of the product. The reaction time of 10-15h ensures that the polymerization reaction is fully carried out. During this period of time, the monomer molecules can be fully converted into polymer chains to form a stable cross-linked network structure. At the same time, a longer reaction time also helps to reduce the residues of unreacted monomers and by-products, and improve the purity and quality of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0023] Figure 1 FTIR test graphs of different reaction monomers and synthesized PSAT zwitterionic composite hydrogel; Figure 2 The uniaxial tensile test results of the zwitterionic composite hydrogels prepared in Examples 1 to 3 of the present invention; Figure 3 It is an adhesion test curve diagram of the zwitterionic composite hydrogels prepared in Examples 1 to 3 of the present invention and the PST prepared in Comparative Example 1; Figure 4 The antibacterial performance test results of the zwitterionic composite hydrogels prepared in Examples 1 to 3 of the present invention, wherein (a) is a schematic diagram of the hydrogel antibacterial zone, and (b) is a diagram of the diameter measurement of the hydrogel antibacterial zone; Figure 5 The hemolysis diagram of the zwitterionic composite hydrogel prepared in Examples 1 to 3 of the present invention; Figure 6 Schematic diagram of hydrogel as wound dressing. DETAILED DESCRIPTION
[0024] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0025] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0026] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0027] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0028] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0029] The present invention provides a method for preparing a zwitterionic composite hydrogel adhesive, comprising the following steps: S1: Dissolve the reaction monomers SBMA and AMPS in water, and ultrasonically oscillate them at room temperature to fully dissolve them. Then add THMA, stir until the mixture is evenly mixed, then add the initiator and cross-linking agent, and ultrasonically dissolve them to obtain a precursor solution. According to the mass fraction, the ratio of the reaction monomer SBMA to AMPS is (9-5): (1-5). The ratio of the THMA to SBMA and AMPS is 1: (9-5): (1-5). The ratio of the PVA to SBMA and AMPS is 20: (9-5): (1-5). The ratio of SBMA to AMPS and initiator is (25-13): (2-13): 1. The ratio of SBMA to AMPS and crosslinker is (300-160): (30-160): 1. The crosslinker is N, N'-methylenebisacrylamide and borax; according to the mass fraction, the ratio of N, N'-methylenebisacrylamide to borax is (1-5): (1-10).
[0030] S2: adding the PVA aqueous solution to the precursor solution, and performing a free radical polymerization reaction at 35-45° C. for 10-15 hours to obtain the zwitterionic composite hydrogel adhesive.
[0031] In step S2, the obtained polymer solution can be uniformly injected into the glass plate mold through a 5 mL syringe to ensure uniform distribution.
[0032] The preparation process of the PVA aqueous solution is as follows: PVA is dissolved in water, and heated and stirred at 90-100° C. for 5-8 hours to obtain the PVA aqueous solution. The invention also discloses a zwitterionic composite hydrogel adhesive prepared by the method. The zwitterionic composite hydrogel adhesive has a tensile strength of 0.07-0.14 MPa and an adhesion force of 20-33 KPa.
[0033] In a further preferred specific embodiment, the present invention provides a method for preparing a zwitterionic composite hydrogel adhesive, comprising the following steps: Step 1, dissolve 20 parts of PVA in 180 ml of deionized water, heat and stir at 90-100° C. for 5 hours to obtain 10 wt % PVA solution A, which is set aside for later use.
[0034] Step 2, dissolve the reaction monomers SBMA and AMPS in 6 parts of deionized water, and dissolve them by ultrasonic oscillation at room temperature for 5 minutes to form an aqueous solution. Then, add 1 part of THMA to the solution, and after the solution is fully mixed, add 0.4 parts of initiator APS and 15~25 μL of cross-linking agent MBAA and 10~20 μL of borax, and dissolve them by ultrasonic oscillation in a water bath for 10 minutes to obtain precursor solution B.
[0035] Step 3, 3 parts of PVA solution and precursor solution B are mixed and stirred for 10-15 minutes, and then the mixed solution is injected into a reaction cell consisting of a pair of glass plates with a spacing of 2 mm. In an oven at 35 to 45°C, a free radical polymerization reaction is carried out for 10-15 hours to obtain a zwitterionic polymerized hydrogel adhesive.
[0036] The initiator is ammonium persulfate, and the cross-linking agent is N,N'-methylenebisacrylamide and borax; the contents of the initiator and the cross-linking agent are 0.4 parts and 15-25 μL respectively (mass concentration is 2%).
[0037] The present invention prepares a hydrogel by a one-pot method by combining anionic monomer 2-acrylamide-2-methylpropane sulfonate (AMPS) into a double-layer network of zwitterion (SBMA) and polyvinyl alcohol (PVA). Polyvinyl alcohol (PVA) has abundant cross-linking sites and multiple hydrogen bonds. Zwitterion [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonate propyl)ammonium hydroxide (SBMA) has cationic and anionic groups and has a high dipole moment. This strong dipole property forms an adhesion effect with the surface through ion-dipole or dipole-dipole interaction, and the chain-chain association between the polymers can provide physical cross-linking to enhance the mechanical properties of the water adhesive. Reactive monomer N-[tris(hydroxymethyl)methyl]acrylamide (THMA) can provide hydrogen bonding for the polymer, thereby further promoting adhesion. The mechanical properties, adhesion properties, etc. of the zwitterion composite hydrogel adhesive are mainly achieved by the ratio of reactive monomers SBMA and AMPS. In the present invention, the selected polyvinyl alcohol (PVA) has abundant cross-linking sites. The zwitterion [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonatepropyl)ammonium hydroxide (SBMA) has strong dipole properties and can provide physical crosslinking through interchain association to enhance mechanical properties. At the same time, the cationic quaternary amine group gives the adhesive a certain antibacterial property. The reactive monomer N-[tris(hydroxymethyl)methyl]acrylamide (THMA) can provide triple hydrogen bonding and load-sharing effects, thereby improving adhesion. 2-Acrylamide-2-methylpropane sulfonic acid (AMPS), as an anionic monomer, has ionic synergistic effects with zwitterions, promotes ion migration, and improves conductivity.
[0038] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0039] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0040] Example 1 A method for preparing a zwitterionic composite hydrogel adhesive comprises the following steps: Step 1. First, weigh 20 parts of polyvinyl alcohol (PVA) and dissolve it in 180 parts of deionized water. The process is carried out under heating conditions at 90°C and stirred for 5 hours to ensure that the PVA is completely dissolved and forms a uniform 10wt% PVA solution A for subsequent use.
[0041] Step 2, weigh 9 parts of the reaction monomer [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfonic acid propyl) ammonium hydroxide (SBMA) and 1 part of 2-acrylamide-2-methylpropane sulfonic acid (AMPS), and dissolve them in 6 parts of deionized water. At room temperature, use an ultrasonic oscillator to oscillate for 5 minutes to ensure that the reaction monomer is fully dissolved and forms a uniform aqueous solution. Subsequently, add 1 part of N-[tris(hydroxymethyl)methyl]acrylamide (THMA) and mix well. Then, add 0.4 parts of initiator APS and 15µL of cross-linker N,N'-methylenebisacrylamide (MBAA) and 10µL of borax. Place the solution in a water bath and ultrasonically treat for 10 minutes to ensure that each component is fully reacted to obtain precursor solution B.
[0042] Step 3. Finally, the three parts of PVA solution and precursor solution B were fully mixed and stirred for 10 min. After ensuring uniformity, the mixed solution was injected into a reaction plate consisting of a pair of glass plates with a spacing of 2 mm. The reaction plate was placed in an oven at 35 to 45 ° C and subjected to a free radical polymerization reaction for 10 h to obtain the desired zwitterionic polymerized hydrogel adhesive. The hydrogel adhesive exhibited excellent adhesive properties and biocompatibility in a variety of application scenarios. The synthesized zwitterionic composite hydrogel can be expressed as PS5A5T.
[0043] Example 2 Calculated by weight, the difference from Example 1 is that the ratio of SBMA to AMPS is 7:3, and the synthesized zwitterionic composite hydrogel can be expressed as PS7A3T.
[0044] Example 3 Calculated by weight, the difference from Example 1 is that the ratio of SBMA to AMPS is 9:1, and the synthesized zwitterionic composite hydrogel can be expressed as PS9A1T.
[0045] Comparative Example 1 The difference between this comparative example and Example 1 is that AMPS is not added, and the mass ratio of PVA, SBMA and THMA is 8:6:5. The prepared sample is marked as PST.
[0046] Figure 1 The FTIR test diagrams of different reaction monomers and synthesized PSAT zwitterionic composite hydrogels show that the broad peak of the stretching vibration of hydroxyl (OH) is located at 3400 cm−1 , while the OH stretching vibration peaks of THMA, SBMA and PVA are 3431 cm −1 、3564 cm −1 and 3400 cm −1 After hydrogel synthesis, the OH stretching vibration of PSAT hydrogel shifted to a lower wavenumber (3000 cm −1 ). The formation of hydrogen bonds within or between molecules leads to a decrease in the mechanical constant of the chemical bond, which results in a low-wavenumber shift of the vibration frequency. The shift of the OH absorption band to low wavenumbers indicates that strong hydrogen bonds are formed between THMA, SBMA, and PVA after the hydrogel synthesis. In addition, the 1193 cm −1 The characteristic peak of the sulfonic acid group at the SBMA structure weakened, indicating that the negatively charged - SO 3 - The group is protonated.
[0047] Figure 2 The results of uniaxial tensile tests of zwitterionic composite hydrogels prepared in Examples 1 to 3 of the present invention are shown. As can be seen from the figure, the tensile strength of the PS9A1T hydrogel is 0.13 MPa. The fracture strain is 385%. As the mass ratio of SBMA to AMPS changes, the degree of crosslinking in the hydrogel network changes, and the increase of negatively charged AMPS monomers in the system will partially shield the dipole-dipole interaction in SBMA. Therefore, the PS5A5T hydrogel will become softer and more stretchable, with a tensile strength of 0.06 MPa. The fracture strain is 470%.
[0048] Figure 3 The adhesion test curves of the zwitterionic composite hydrogels prepared in Examples 1 to 3 of the present invention and the PST prepared in Comparative Example 1 show the results of the adhesion performance test of PSAT zwitterionic composite hydrogel adhesives with different ratios, reflecting the differences in adhesion strength and stability of samples of each ratio, and providing a basis for optimizing the adhesive formulation. As can be seen from the figure, the adhesion strength varies with the different ratios of SBMA to AMPS. The stability and strong adhesion of PSAT hydrogel to different substrates can be attributed to the multiple covalent / non-covalent interactions of the hydrogel, such as hydrogen bonds, borate bonds, and ionic interactions. The positive and negative charges of the zwitterions produce extremely high dipole moments, which makes the zwitterionic hydrogel have excellent adhesion. The three hydroxyl groups of THMA introduced into the system can form high-density hydrogen bonds and increase the toughness of the interface. With the intervention of the anionic monomer, the –SO 3– Groups can be in the network with –N in SBMA + (R) 3 However, with the increase of the total concentration of AMPS, the –SO 3–As the number of groups increases, the electrostatic state of the hydrogel system changes, resulting in a decrease in the adhesion strength of the hydrogel. This indicates that the adhesion properties of polyanionic hydrogels are closely related to the electrostatic state of the hydrogel and the substrate.
[0049] Figure 4 The antibacterial performance test results of the zwitterionic composite hydrogels prepared in Examples 1 to 3 of the present invention are shown, wherein (a) is a schematic diagram of the hydrogel antibacterial circle, and (b) is a diagram of the diameter of the hydrogel antibacterial circle measurement. This figure shows the performance of PSAT zwitterionic composite hydrogel adhesives with different ratios in the antibacterial performance test, evaluates its inhibitory effect on a variety of bacteria, and verifies its antibacterial potential in biomedical materials. As shown in the figure, the zwitterionic composite hydrogel prepared by the present invention has a strong inhibitory effect on both bacterial colonies. The cationic quaternary ammonium group attracts the anionic part of the bacterial membrane through strong Coulomb attraction, which can kill a large number of bacteria. At the same time, the sulfonic acid group of AMPS in the system may reduce the pH value of the hydrogel surface or damage the bacterial membrane. Therefore, the antibacterial ability may be attributed to the synergistic effect between the zwitterionic SBMA and the sulfonic acid group in AMPS, but too much AMPS will carry a large amount of negative charge, thereby shielding part of the positive charge of the zwitterionic ion, reducing the attraction of the hydrogel to the bacterial membrane, and ultimately leading to a decrease in antibacterial performance.
[0050] Figure 5 The hemolysis diagram of the zwitterionic composite hydrogel prepared in Examples 1 to 3 of the present invention. The figure shows the test results of the PSAT zwitterionic composite hydrogel adhesive with different ratios in terms of blood compatibility, indicating the degree of its influence on blood components, and provides an important reference for its application in the field of biomedicine. As can be seen from the figure, the supernatant of all hydrogel groups is almost colorless, similar to the control group of PBS solution, and contrasts with the bright red solution of the positive control group. The quantitative test results show that the hemolysis rate of the hydrogel group is less than 5%, proving that the prepared hydrogel has good blood compatibility.
[0051] Figure 6 This is a schematic diagram of hydrogel as a wound dressing. As can be seen from the figure, the hydrogel adhesive can adhere well to the wound defect of mice, fit completely with the skin, and has antibacterial and skin growth-promoting effects.
[0052] Example 4 A method for preparing a zwitterionic composite hydrogel adhesive comprises the following steps: S1: Dissolve the reaction monomers SBMA and AMPS in water, and ultrasonically oscillate them at room temperature to fully dissolve them. Then add THMA, stir until the mixture is evenly mixed, then add the initiator and cross-linking agent, and ultrasonically dissolve them to obtain a precursor solution. S2: dissolving PVA in water, heating and stirring at 90° C. for 8 hours to obtain the PVA aqueous solution; adding the PVA aqueous solution to the precursor solution, performing free radical polymerization at 35° C. for 15 hours to obtain the zwitterionic composite hydrogel adhesive.
[0053] In the above preparation process, the ratio of the reaction monomer SBMA to AMPS is 9:1 by weight. The ratio of THMA to SBMA and AMPS is 1:9:1. The ratio of PVA to SBMA and AMPS is 20:9:1. The ratio of SBMA to AMPS and initiator is 20:2:1. The ratio of SBMA to AMPS and crosslinker is 280:30:1. The crosslinker is N,N'-methylenebisacrylamide and borax; the ratio of N,N'-methylenebisacrylamide to borax is 1:1 by weight.
[0054] The tensile strength of the zwitterionic composite hydrogel adhesive prepared in this example is 0.07 MPa, and the adhesion is 20 KPa.
[0055] Example 5 A method for preparing a zwitterionic composite hydrogel adhesive comprises the following steps: S1: Dissolve the reaction monomers SBMA and AMPS in water, and ultrasonically oscillate them at room temperature to fully dissolve them. Then add THMA, stir until the mixture is evenly mixed, then add the initiator and cross-linking agent, and ultrasonically dissolve them to obtain a precursor solution. S2: dissolving PVA in water, heating and stirring at 100° C. for 5 h to obtain the PVA aqueous solution; adding the PVA aqueous solution to the precursor solution, and performing free radical polymerization at 45° C. for 10 h to obtain the zwitterionic composite hydrogel adhesive.
[0056] In the above preparation process, the ratio of the reaction monomer SBMA to AMPS is 5:5 by weight. The ratio of THMA to SBMA and AMPS is 1:5:5. The ratio of PVA to SBMA and AMPS is 20:5:5. The ratio of SBMA to AMPS and initiator is 13:13:1. The ratio of SBMA to AMPS and crosslinker is 160:160:1. The crosslinker is N,N'-methylenebisacrylamide and borax; the ratio of N,N'-methylenebisacrylamide to borax is 2:5 by weight.
[0057] The tensile strength of the zwitterionic composite hydrogel adhesive prepared in this example is 0.13 MPa, and the adhesion force is 33 KPa.
[0058] Example 6 A method for preparing a zwitterionic composite hydrogel adhesive comprises the following steps: S1: Dissolve the reaction monomers SBMA and AMPS in water, and ultrasonically oscillate them at room temperature to fully dissolve them. Then add THMA, stir until the mixture is evenly mixed, then add the initiator and cross-linking agent, and ultrasonically dissolve them to obtain a precursor solution. S2: dissolving PVA in water, heating and stirring at 95° C. for 6 hours to obtain the PVA aqueous solution; adding the PVA aqueous solution to the precursor solution, performing free radical polymerization at 40° C. for 12 hours to obtain the zwitterionic composite hydrogel adhesive.
[0059] In the above preparation process, the ratio of the reaction monomer SBMA to AMPS is 8:3 by weight. The ratio of THMA to SBMA and AMPS is 1:8:3. The ratio of PVA to SBMA and AMPS is 20:8:3. The ratio of SBMA to AMPS and initiator is 17:6:1. The ratio of SBMA to AMPS and crosslinker is 240:90:1. The crosslinker is N,N'-methylenebisacrylamide and borax; the ratio of N,N'-methylenebisacrylamide to borax is 3:7 by weight.
[0060] The tensile strength of the zwitterionic composite hydrogel adhesive prepared in this example is 0.14 MPa, and the adhesion is 25 KPa.
[0061] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a zwitterionic composite hydrogel adhesive, characterized in that: The following steps are involved: S1: Dissolve the reaction monomers SBMA and AMPS in water, and ultrasonically oscillate them at room temperature to fully dissolve them. Then add THMA, stir until the mixture is evenly mixed, then add the initiator and cross-linking agent, and ultrasonically dissolve them to obtain a precursor solution. S2: adding the PVA aqueous solution to the precursor solution to carry out a free radical polymerization reaction to obtain the zwitterionic composite hydrogel adhesive.
2. The method for preparing a zwitterionic composite hydrogel adhesive according to claim 1, characterized in that: Calculated by weight, the ratio of the reaction monomers SBMA and AMPS is (9-5):(1-5).
3. The method for preparing a zwitterionic composite hydrogel adhesive according to claim 1, characterized in that: In terms of mass fractions, the ratio of THMA to SBMA and AMPS is 1:(9-5):(1-5).
4. The method for preparing a zwitterionic composite hydrogel adhesive according to claim 1, characterized in that: In terms of mass fractions, the ratio of PVA to SBMA and AMPS is 20:(9-5):(1-5).
5. The method for preparing a zwitterionic composite hydrogel adhesive according to claim 1, characterized in that: In terms of mass fractions, the ratio of SBMA to AMPS and initiator is (25~13):(2~13):
1.
6. The method for preparing a zwitterionic composite hydrogel adhesive according to claim 1, characterized in that: In terms of weight fractions, the ratio of SBMA to AMPS and the cross-linking agent is (300~160):(30~160):
1.
7. The method for preparing a zwitterionic composite hydrogel adhesive according to claim 1, characterized in that: The cross-linking agent is N,N'-methylenebisacrylamide and borax; in terms of mass fraction, the ratio of N,N'-methylenebisacrylamide to borax is (1-5):(1-10).
8. The method for preparing a zwitterionic composite hydrogel adhesive according to claim 1, characterized in that: The preparation process of the PVA aqueous solution is as follows: PVA is dissolved in water, and heated and stirred at 90-100° C. for 5-8 hours to obtain the PVA aqueous solution.
9. The method for preparing a zwitterionic composite hydrogel adhesive according to claim 1, characterized in that: The reaction temperature of the free radical polymerization reaction is 35-45° C., and the reaction time is 10-15 hours.
10. A zwitterionic composite hydrogel adhesive, characterized in that: The zwitterionic composite hydrogel adhesive is prepared by the method described in any one of claims 1 to 9; the tensile strength of the zwitterionic composite hydrogel adhesive is 0.07 to 0.14 MPa, and the adhesion is 20 to 33 KPa.
Citation Information
Patent Citations
A cyanoacrylate adhesive and preparation method thereof
CN115678441B
Antibacterial hemostatic fibrin adhesive and preparation method thereof
CN116212099A
High-strength double-network zwitter-ion hydrogel and production method thereof
CN109971042A
Multifunctional sodium alginate-P (SBMA-co-AAm) ionic conductive hydrogel and preparation method thereof
CN111154037A
Medical zwitterionic polymer hydrogel adhesive and preparation method thereof
CN114456313A
Cited By
Self-lubricating hydrogel titanium alloy bionic joint bearing interface and preparation method thereof
CN120285287A
Preparation of green and environment-friendly high-viscosity conductive material
CN120442185A
Tissue adhesive as well as preparation method and application thereof
CN121891591A